ISOLATION AND IDENTIFICATION OF BACILLUS SPP. FROM COMPOST MATERIAL, COMPOST AND MUSHROOM CASING SOIL ACTIVE AGAINST TRICHODERMA SPP. - Stanojević, Olja; Milijašević-Marčić, Svetlana; Potočnik, Ivana; Stepanović, Miloš; Dimkić, Ivica; Stanković, Slaviša; Berić, Tanja (Archives of Biological Sciences, 2016)
The isolation of bacteria was carried out from samples of straw and chicken manure, compost at various stages of the composting process and casing soil used for growing button mushrooms. A preliminary screening of 108 bacterial isolates for antagonistic activity against Trichoderma aggressivum f. europaeum showed that 23 tested isolates inhibited mycelial growth of the pathogenic fungus. Further screening with four indicator isolates of fungi revealed that all 23 bacterial isolates inhibited the growth of T. aggressivum f. europaeum, T. harzianum and T. koningii, while only 13 isolates inhibited the growth of T. atroviride. T. aggressivum f. europaeum proved to be the most sensitive, with many bacterial isolates generating a high percentage of growth inhibition. Only two bacterial isolates (B-129 and B-268) were successful in inhibiting the growth of all 4 tested pathogens. All 23 bacterial isolates were characterized as Gram-positive and catalase-positive and were subjected to molecular identification based on the partial sequence, the hypervariant region of the 16S rDNA. It was shown that the obtained bacterial strains belong to Bacillus subtilis, B. amyloliquefaciens, B. licheniformis and B. pumilus species. DOI: 10.2298/ABS151104073S Key words: Agaricus bisporus; Bacillus; biocontrol; green mold; hypervariant region Received: November 4, 2015; Revised: December 25, 2015; Accepted: January 21, 2016; Published online: August 9, 2016 How to cite this article: Stanojević O, Milijašević-Marčić S, Potočnik I, Stepanović M, Dimkić I, Stanković S, Berić T. Isolation and identification of Bacillus spp. from compost material, compost and mushroom casing soil active against Trichoderma spp.. Arch Biol Sci. 2016;68(4):845-52.